the marital harmony according to some variable (age, marriage duration, sex & living) - Ghazala OULADALAID; Selami BAHI; Tedjani BENTAHAR (Social Sciences Journal, 2022)
The study aims to know the level of marital harmony among a sample of teachers in terms of (sex, marriage duration, age &living). Sample included 109 teachers from metlili.We used the descriptive study method with measuring in the scale of marital harmony, which consisted of 32 items prepared by (Sapner). The data were processed using the SPSS21 program, using appropriate statistical methods. The study ends to the following: The levels of marital harmony among teachers scored (high). There are statistical differences in the level of marital harmony among teachers due to variable of Marriage duration. There are no significant statistic differences in the level of marital harmony among teachers due to variables of sex ، living and age).